The complex interactions of context availability, polysemy, word frequency, and orthographic variables during lexical processing. - Rice, Caitlin A.; Tokowicz, Natasha; Fraundorf, Scott H.; Liburd, Teljer L. (Memory & Cognition, 2019)
In this study we examined the interactions of context availability, polysemy, word frequency, and orthographic neighborhood variables during lexical processing. Context availability and polysemy interacted, in that words that were both lower in context availability and had fewer related senses were especially disadvantaged, as was originally reported by Tokowicz and Kroll (2007). Word frequency interacted with both polysemy and context availability, in that the effects of polysemy and context availability were stronger for lower-frequency words. Finally, orthographic neighborhood size and frequency both interacted with polysemy: the effect of polysemy was greater for words with smaller orthographic neighborhoods and a greater number of higher-frequency neighbors. These findings provide support for the context availability hypothesis (Schwanenflugel & Shoben, 1983). Specifically, the feedback activation account (Hino & Lupker, 1996) offers a mechanistic explanation of our findings that is rooted in feedback from semantic to orthographic representations.